Coating with low solar radiation absorptivity and coating method

Through the combination of TiO2, BaSO4, ZnO and Eu2O and the use of Fe203-MnO2-NiO-Co203 composite nano powder, combined with the combination of potassium silicate modified inorganic pigment and dispersing additives, the existing thermal insulation coatings are solved. The poor solar radiation temperature reduction effect and ultraviolet aging problems have achieved efficient heat insulation and anti-ultraviolet aging performance, extending the service life of the charging pile shell.

CN119286395APending Publication Date: 2025-01-10HENAN LONGXIANG ELECTRICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411618799.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing thermal insulation coatings are difficult to effectively cool down under solar radiation and are susceptible to ultraviolet aging, resulting in unsatisfactory thermal insulation effect, affecting the normal operation and service life of charging piles.

Method used

Using reflective insulation materials combined with TiO2, BaSO4, ZnO and Eu2O, combined with Fe203-MnO2-NiO-Co203 composite nanopowder and barite, inorganic pigment and silane coupling agent are modified by potassium silicate. , the compounding of OP-10 emulsifier forms a high reflectivity and anti-UV aging coating, and is coated through air spraying or scraping.

Benefits of technology

It significantly improves the solar radiation reflectance and infrared emissivity of the coating, enhances the anti-UV aging performance, extends the service life of the coating, and significantly improves the thermal insulation and protection effect of the charging pile shell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132933890000051
    Figure BDA0005132933890000051
  • Figure BDA0005132933890000081
    Figure BDA0005132933890000081
Patent Text Reader

Abstract

The invention relates to a coating with low solar radiation absorptivity and a coating method. The coating comprises the following components in percentage by weight: 18-22 wt% of a reflective thermal insulation material, 5-7 wt% of an infrared emission material, 13-15 wt% of a modified inorganic pigment, 4-6 wt% of an organic binder, 4-6 wt% of a thermal insulation aid, 1-3 wt% of a dispersing aid and the balance of a solvent, the reflective thermal insulation material is prepared from TiO2, BaSO4, ZnO and Eu2O according to the mass ratio of 1 to (0.8 to 1.0) to (0.5 to 0.7) to (0.3 to 0.5). The heat insulation protection effect of the heat insulation coating on the charging column can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coatings, and in particular to a coating with low solar radiation absorption rate and a coating method. Background Art

[0002] A charging pile refers to a charging device that provides energy for electric vehicles. Its function is similar to that of a gas pump in a gas station. It can be fixed on the ground or on a wall and installed in parking lots or charging stations in public buildings and residential areas. It can charge various models of electric vehicles according to different voltage levels.

[0003] Since the charging column is equipped with power distribution equipment and lines, the working environment of the power distribution equipment and lines needs to maintain a relatively suitable temperature. However, since the shell of the charging pile is made of metal material, for charging piles installed outdoors, under the scorching sun, the shell of the charging pile will be subjected to a large amount of solar radiation heat and transferred to the shell, causing the working environment temperature of the power distribution equipment and lines in the charging column to be too high, affecting the normal operation and service life of the charging pile.

[0004] At present, in order to improve the high temperature resistance of charging piles, thermal insulation coatings are usually applied to the outside of the charging pile shell to form a thermal insulation coating. Thermal insulation coatings usually include pigments, reflective materials such as titanium dioxide, acrylic acid and water, etc. The coating formed by the above-mentioned thermal insulation coatings can reduce the heat accumulation inside the charging pile by blocking and reflecting the solar radiation heat, thereby improving the working environment of the distribution equipment and lines to a certain extent.

[0005] The coating formed by applying the above-mentioned thermal insulation material on the shell of the charging pile can achieve a cooling effect of 3-6°C. However, the cooling effect is still not ideal for some hot and humid areas, which limits the application scenarios of the charging piles. In addition, in current practical applications, the coating is aged due to ultraviolet light, which makes the coating prone to cracking or even rupture, resulting in the thermal insulation protection effect of the thermal insulation coating on the charging column being not ideal. Summary of the invention

[0006] In order to enhance the heat insulation protection effect of the heat insulation coating on the charging column, the present application provides a coating with low solar radiation absorption rate and a coating method.

[0007] In the first aspect, the present application provides a coating with low solar radiation absorption rate using the following technical solution: A coating with low solar radiation absorption rate, comprising the following components and their contents: 18-22wt% of reflective heat-insulating material, 5-7wt% of infrared emitting material, 13-15wt% of modified inorganic pigment, 4-6wt% of organic binder, 4-6wt% of heat-insulating auxiliary agent, 1-3wt% of dispersing auxiliary agent, and the balance is solvent; The reflective heat-insulating material comprises TiO2, BaSO4, ZnO and Eu2O in a mass ratio of 1: (0.8-1.0): (0.5-0.7): (0.3-0.5).

[0008] By adopting the above technical solution, since TiO2 and ZnO only absorb ultraviolet light with a wavelength below 385nm, they have a strong solar radiation reflectivity, and since TiO2 and BaSO4 are compatible, compounding TiO2 and BaSO4 can further improve the solar radiation reflectivity of the coating. Secondly, ultraviolet light with a wavelength below 385nm can break the chemical bonds of most organic binders, so TiO2 and ZnO can well screen the damage of ultraviolet light to the binder, so that the coating maintains good optical properties while improving the anti-ultraviolet aging performance of the coating.

[0009] However, since the absorption band of TiO2 is mainly concentrated in 310-380nm, the absorption band of ZnO is mainly concentrated in 290-320nm, and the absorption band of Eu2O is mainly concentrated in 190-230nm, compounding TiO2, ZnO and Eu2O can absorb ultraviolet light more comprehensively, so as to further improve the anti-ultraviolet aging performance of the coating.

[0010] The reflective heat-insulating material obtained by compounding TiO2, BaSO4, ZnO and Eu2O can improve the coating's reflectivity to solar radiation in the 0.3-3.0μm band, and can effectively shield the damage of ultraviolet light to the binder, so that the coating maintains good optical properties while improving the coating's anti-ultraviolet aging performance, thereby reducing the possibility of the coating being aged by ultraviolet rays and causing the coating to crack or even fall off, thereby improving the heat-insulating protection effect of the thermal insulation coating on the charging column.

[0011] Optionally, the infrared emitting material includes Fe203-MnO2-NiO-Co203 composite nano powder, barite and brucite in a mass ratio of 1:(0.3-0.5):(0.1-0.3).

[0012] By adopting the above technical solution, because the transition metal oxide series infrared radiation materials have a complex inverse spinel phase or mixed spinel phase, the material has a higher emissivity and can better dissipate the radiant heat of the charging pile. Barite and brucite can change the Fe203-MnO2-NiO-Co203 composite nanopowder from black to gray to further improve the emissivity of the material. Therefore, the compounding of Fe203-MnO2-NiO-Co203 composite nanopowder with barite and brucite can improve the reflectivity of the coating to solar radiation in the 0.3-3.0μm band and improve the thermal insulation protection effect of the thermal insulation coating on the charging column.

[0013] Optionally, the method for preparing the infrared emitting material comprises the following steps: Mix Fe203, MnO2, NiO and Co203 and wet-grind them for 15-18 hours; take out, dry, grind and sieve to obtain powder; then keep the powder calcined at 1100-1200°C for 1-2 hours, and grind to obtain Fe203-MnO2-NiO-Co203 composite nanopowder; wet-grind the Fe203-MnO2-NiO-Co203 composite nanopowder with barite powder and brucite powder in a mass ratio, dry, crush, grind and sieve the mixed product to obtain an infrared emitting material.

[0014] Optionally, the modified inorganic pigment is obtained by coating and modifying an inorganic pigment with potassium silicate.

[0015] By adopting the above technical solution, inorganic pigments, due to the various colors, usually increase the solar radiation absorption rate of the coating in certain bands, resulting in a poor thermal insulation effect of the coating. By coating and modifying the inorganic pigment particles with potassium silicate, the solar radiation reflectivity of the inorganic pigment can be greatly improved to reduce the impact of the addition of the pigment on the reflectivity of the coating; and the dispersion uniformity of the inorganic pigment in the coating can be improved to improve the thermal insulation protection effect of the formed coating on the charging column.

[0016] Optionally, the inorganic pigment is selected from at least one of titanium dioxide, aluminum powder, red iron oxide, lead chrome yellow, ultramarine and cobalt blue.

[0017] By adopting the above technical solution, the above inorganic pigments will not change their own characteristics after being modified, so as to better enhance the color of the pattern on the charging pile shell.

[0018] Optionally, the organic binder is selected from at least one of methyl silicone resin, polymethylsiloxane and acrylic resin.

[0019] Optionally, the dispersing aid includes a silane coupling agent and an OP-10 emulsifier in a mass ratio of 1:(0.4-0.6).

[0020] By adopting the above technical solution, the addition of silane crosslinker can improve the surface wettability of organic materials, improve the compatibility of organic polymer surfaces with inorganic material surfaces, and the functional groups on the surface of organic polymers and the organic functional groups on the surface of inorganic materials treated with silane form hydrogen bonds, thereby improving the adhesion between the coating and the substrate. The OP-10 emulsifier is a non-ionic surfactant. The addition of the emulsifier enables the prepared coating to form a dispersed system with a certain stability, improves the coagulation of pigment particles, reduces interfacial tension, and improves the stability of the coating. The compound use of silane crosslinker and OP-10 emulsifier can effectively improve the uniformity and stability of the coating.

[0021] Optionally, the thermal insulation aid comprises hollow microspheres and polyurethane in a mass ratio of 1:(1.3-1.5).

[0022] In a second aspect, the present application provides a method for preparing a coating with low solar radiation absorption rate using the following technical solution: A method for preparing a coating with low solar radiation absorption rate comprises the following steps: The above-mentioned reflective heat-insulating material, infrared emitting material, modified inorganic pigment, organic binder and heat-insulating aid are sequentially added to the solvent and stirred for 1-2 minutes, then a dispersing aid is added and stirred for 1-2 minutes, and finally ultrasonically dispersed for 1-2 hours to obtain a coating.

[0023] By adopting the above technical solution, the components in the coating can be dispersed more evenly, so as to further improve the uniformity and stability of the coating.

[0024] In a third aspect, the present application provides a coating method for a coating with low solar radiation absorption rate, which adopts the following technical solution: A method for preparing a coating with low solar radiation absorption rate comprises the following steps: First, polish the substrate, then use ethanol to ultrasonically clean the substrate for 1 hour, and then dry it for later use; Then the prepared coating is coated on the substrate by air spraying, scraping or brushing, with a coating thickness of 80-110 μm, and then cured at room temperature for 7-10 days.

[0025] By adopting the above technical solution, the substrate is first processed and then coated according to the above thickness and curing conditions, so that the coating can be more firmly adhered to the substrate, thereby enhancing the thermal insulation protection effect of the thermal insulation coating on the charging column.

[0026] In summary, the present application includes at least one of the following beneficial technical effects: 1. The reflective heat-insulating material obtained by compounding TiO2, BaSO4, ZnO and Eu2O can improve the coating's reflectivity to solar radiation in the 0.3-3.0μm band, and can well shield the damage of ultraviolet light to the binder, so that the coating maintains good optical properties while improving the coating's anti-ultraviolet aging performance, thereby reducing the possibility of cracking or even falling off of the coating due to aging caused by ultraviolet rays, thereby improving the heat-insulating protection effect of the heat-insulating coating on the charging column; 2. The Fe203-MnO2-NiO-Co203 composite nanopowder can dissipate the radiant heat of the charging pile. The introduction of barite and brucite can change the Fe203-MnO2-NiO-Co203 composite nanopowder from black to gray, thereby improving the reflectivity of the coating to solar radiation in the 0.3-3.0μm band; 3. By coating and modifying the inorganic pigment particles with potassium silicate, the solar radiation reflectivity of the inorganic pigment can be greatly improved to reduce the impact of the addition of the pigment on the reflectivity of the coating; and the dispersion uniformity of the inorganic pigment in the coating can be improved to enhance the heat insulation protection effect of the formed coating on the charging column. DETAILED DESCRIPTION

[0027] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0028] 1. Implementation Embodiment 1: A coating with low solar radiation absorption rate, comprising the following components and their contents: 18wt% of reflective heat-insulating material, 5wt% of infrared emitting material, 13wt% of modified inorganic pigment, 4wt% of methyl silicone resin, 4wt% of heat-insulating auxiliary agent, 1wt% of dispersing auxiliary agent, and the balance is solvent; The reflective heat-insulating material includes TiO2, BaSO4, ZnO and Eu2O in a mass ratio of 1:0.9:0.6:0.4; The dispersing aids include silane coupling agent and OP-10 emulsifier in a mass ratio of 1:0.5, the silane coupling agent is purchased from Shandong Shengcang Chemical Technology Co., Ltd., and the OP-10 emulsifier is purchased from Hai'an Petrochemical Plant in Jiangsu Province; The heat-insulating additives include hollow microspheres and polyurethane in a mass ratio of 1:1.4, and the hollow microspheres are purchased from Lingshou County Shengfei Mineral Products Processing Plant; The solvent includes xylene and acetone in a mass ratio of 1:1.

[0029] The infrared emitting material includes Fe203-MnO2-NiO-Co203 composite nano powder, barite and brucite in a mass ratio of 1:0.4:0.2; The method for preparing the infrared emitting material comprises the following steps: Mix Fe203, MnO2, NiO and Co203 in a mass ratio of 1:1:1:1.3 and wet grind for 15-18 hours; take out, dry, grind and sieve to obtain powder; then calcine the powder at 1150°C for 2 hours, and grind to obtain Fe203-MnO2-NiO-Co203 composite nanopowder; The Fe203-MnO2-NiO-Co203 composite nano powder, barite powder and brucite powder are mixed and wet-ground according to a mass ratio. After drying, the mixed product is crushed, ground and sieved to obtain an infrared emitting material.

[0030] The modified inorganic pigment is obtained by coating and modifying the inorganic pigment with potassium silicate; The preparation method of the modified inorganic pigment comprises the following steps: Weigh 50g of titanium dioxide, add anhydrous ethanol, stir and wash thoroughly, filter and dry, and set aside; Potassium silicate, deionized water and alcohol were uniformly mixed in a mass ratio of 1:1.3:0.4, and heated in a water bath to 40°C to obtain a modified treatment solution; The washed inorganic pigment is added to the modified treatment solution, stirred at room temperature for 1.0 h, washed with anhydrous ethanol, filtered, and dried to obtain the modified inorganic pigment.

[0031] Preparation method of coating: The above-mentioned reflective heat-insulating material, infrared emitting material, modified inorganic pigment, methyl silicone resin and heat-insulating auxiliary agent are sequentially added to the solvent and stirred and mixed for 2 minutes, and then a dispersing auxiliary agent is added and stirred and mixed for 2 minutes, and finally ultrasonically dispersed for 1 hour to obtain a coating.

[0032] Coating method: First, polish the substrate, then use ethanol to ultrasonically clean the substrate for 1 hour, and then dry it for later use; The prepared coating was then coated on the substrate using an air spray coating process with a coating thickness of 95 μm, and then cured at room temperature for 8 days.

[0033] Embodiment 2-3: A coating with low solar radiation absorptivity, the differences from Example 1 are shown in Table 1.

[0034] Table 1: Embodiment 4: A coating with low solar radiation absorption rate, which is different from Example 2 in that the mass ratio of TiO2, BaSO4, ZnO and Eu2O in the reflective heat-insulating material is 1:0.8:0.5:0.3.

[0035] Embodiment 5: A coating with low solar radiation absorption rate, which is different from Example 2 in that the mass ratio of TiO2, BaSO4, ZnO and Eu2O in the reflective heat-insulating material is 1:1.0:0.7:0.5.

[0036] Embodiment 6: A coating with low solar radiation absorption rate, which is different from Example 2 in that the mass ratio of Fe203-MnO2-NiO-Co203 composite nanopowder, barite and brucite in the infrared emitting material is 1:0.3:0.1.

[0037] Embodiment 7: A coating with low solar radiation absorption rate, which is different from Example 2 in that the mass ratio of Fe203-MnO2-NiO-Co203 composite nanopowder, barite and brucite in the infrared emitting material is 1:0.5:0.3.

[0038] Embodiment 8: A coating with low solar radiation absorption rate, which is different from Example 2 in that the mass ratio of the silane coupling agent and the OP-10 emulsifier in the dispersing aid is 1:0.4.

[0039] Embodiment 9: A coating with low solar radiation absorption rate, which is different from Example 2 in that the mass ratio of the silane coupling agent and the OP-10 emulsifier in the dispersing aid is 1:0.6.

[0040] Embodiment 10: A coating with low solar radiation absorption rate, which is different from Example 2 in that the mass ratio of hollow microspheres to polyurethane in the thermal insulation auxiliary agent is 1:1.3.

[0041] Embodiment 11: A coating with low solar radiation absorption rate, which is different from Example 2 in that the mass ratio of hollow microspheres to polyurethane in the thermal insulation auxiliary agent is 1:1.5.

[0042] Embodiment 12: A coating with low solar radiation absorption rate, which is different from Example 2 in that the mass ratio of xylene to acetone in the solvent is 1:0.8.

[0043] Embodiment 13: A coating with low solar radiation absorption rate, which is different from Example 2 in that the mass ratio of xylene to acetone in the solvent is 1:1.2.

[0044] 2. Comparison Comparative Example 1: A coating with low solar radiation absorption rate, which is different from Example 2 in that: ZnO in the reflective heat insulation material is replaced by TiO2 in equal amounts.

[0045] Comparative Example 2: A coating with low solar radiation absorption rate, which is different from Example 2 in that: BaSO4 in the reflective heat insulation material is replaced by TiO2 in equal amounts.

[0046] Comparative Example 3: A coating with low solar radiation absorption rate, which is different from Example 2 in that: Eu2O in the reflective heat insulation material is replaced by ZnO in equal amounts.

[0047] Comparative Example 4: A coating with low solar radiation absorption rate, which differs from Example 2 in that equal amounts of barite and brucite are replaced by Fe203-MnO2-NiO-Co203 composite nanopowder.

[0048] Comparative Example 5: A coating with low solar radiation absorption rate, which is different from Example 2 in that an equal amount of OP-10 emulsifier is replaced by a silane coupling agent.

[0049] Comparative Example 6: A coating with low solar radiation absorption rate, which is different from Example 2 in that an equal amount of xylene in the solvent is replaced by acetone.

[0050] 3. Performance Test 1) Sunlight band reflectivity test: The coatings prepared in Examples 1-13 and Comparative Examples 1-6 were tested and analyzed using a UV-Vis-NIR spectrophotometer at an incident angle of 5° (the angle of the light relative to the straight line perpendicular to the film surface). The test wavelength range was set to 0.3-2.5 μm, and the average reflectivity of the entire spectrum was calculated. The test results are shown in Table 2.

[0051] 2) Infrared light band emissivity test: The coatings prepared in Examples 1-13 and Comparative Examples 1-6 were tested and analyzed using a Thermo-IS5 Fourier infrared spectrometer. The test wavelength range was 8-13 μm and the measurement interval was 1 nm. The average value of the absorbance of the coating in the 8-13 μm band was taken as the average absorbance (i.e., average emissivity) of the coating.

[0052] 3) Cooling effect test: The coatings prepared in Examples 1-13 and Comparative Examples 1-6 were exposed to sunlight for the same period of time at the same time during the day, and the temperature was measured using a thermometer to obtain the temperature detection value; and the temperature of the outer wall of the charging pile shell that was not coated with the coating was measured as a blank control group, and the temperature drop value was calculated using the following formula. The calculation results are shown in Table 2.

[0053] 4) Ultraviolet irradiation aging and fading test: The coatings prepared in Examples 1-13 and Comparative Examples 1-6 were tested with UVB-313 fluorescent lamps and NIR near-infrared lamps according to ASTM G154-2012. The samples were continuously irradiated for 200 hours, and the light aging color difference values ​​of the samples in Examples 1-13 and Comparative Examples 1-6 were measured with a colorimeter. The test results are shown in Table 2. Table 2: 4. Results Analysis and Summary Combining Examples 1-3 and Table 2, it can be seen that the weight parts of each component in Examples 1-3 are different. It can be seen from Table 2 that the reflectivity, emissivity and temperature drop value of Example 2 are significantly higher than those of Example 1 and Example 3, and the light aging color difference value is significantly lower than that of Example 1 and Example 3. It can be seen from the above that the coating is prepared according to the weight parts of each component in Example 2, and the obtained coating has better heat insulation effect and anti-ultraviolet aging performance.

[0054] Combining Example 2, Examples 4-5 and Table 2, it can be seen that the mass ratios of TiO2, BaSO4, ZnO and Eu2O in the reflective insulation materials of Examples 4-5 are different from those in Example 2, the reflectivity and temperature drop values ​​of Examples 4-5 are significantly lower than those of Example 2, and the light aging color difference values ​​are significantly higher than those of Example 2.

[0055] In addition, in comparison examples 1-3, in comparison example 1, ZnO in the reflective heat insulation material is replaced by TiO2 in equal amounts, in comparison example 2, BaSO4 in the reflective heat insulation material is replaced by TiO2 in equal amounts, and in comparison example 3, Eu2O in the reflective heat insulation material is replaced by ZnO in equal amounts. As can be seen from Table 2, the reflectivity and temperature drop values ​​of comparison examples 1-3 are much lower than those of example 2, and the light aging color difference values ​​are much higher than those of example 2.

[0056] From the above, it can be concluded that the compound use of TiO2, BaSO4, ZnO and Eu2O can significantly improve the thermal insulation effect and anti-ultraviolet aging performance of the coating; and when the mass ratio of TiO2, BaSO4, ZnO and Eu2O is 1:0.9:0.6:0.4, the thermal insulation effect and anti-ultraviolet aging performance of the obtained coating are relatively better.

[0057] Combining Example 2, Examples 6-7 and Table 2, it can be seen that the mass ratios of Fe203-MnO2-NiO-Co203 composite nanopowder, barite and brucite in the infrared emitting materials of Examples 6-7 are different from those in Example 2. It can be seen from Table 2 that the emissivity and temperature drop values ​​of Examples 6-7 are significantly lower than those of Example 2.

[0058] In combination with Comparative Example 4, in which barite and brucite are replaced with equal amounts of Fe203-MnO2-NiO-Co203 composite nanopowder, it can be seen from Table 2 that the emissivity and temperature drop value of Comparative Example 4 are much lower than those of Example 2.

[0059] From the above, it can be concluded that the compound use of Fe203-MnO2-NiO-Co203 composite nanopowder, barite and brucite can significantly improve the thermal insulation effect and anti-ultraviolet aging performance of the coating; and when the mass ratio of Fe203-MnO2-NiO-Co203 composite nanopowder, barite and brucite is 1:0.4:0.2, the thermal insulation effect and anti-ultraviolet aging performance of the obtained coating are relatively better.

[0060] Combining Example 2, Examples 8-9 and Table 2, it can be seen that the mass ratios of the silane coupling agent and the OP-10 emulsifier in the dispersing aid in Examples 8-9 are different from those in Example 2. As can be seen from Table 2, the reflectivity, emissivity and temperature drop values ​​of Examples 8-9 are significantly lower than those of Example 2, and the light aging color difference values ​​are significantly higher than those of Example 2.

[0061] In combination with Comparative Example 5, in which the OP-10 emulsifier is replaced with an equal amount of a silane coupling agent, it can be seen from Table 2 that the reflectivity, emissivity and temperature drop value of Comparative Example 5 are much lower than those of Example 2, and the light aging color difference value is much higher than that of Example 2.

[0062] From the above, it can be concluded that the compounding of silane coupling agent and OP-10 emulsifier as a dispersing aid can significantly improve the thermal insulation effect and anti-ultraviolet aging performance of the coating; and when the mass ratio of silane coupling agent to OP-10 emulsifier is 1:0.5, the thermal insulation effect and anti-ultraviolet aging performance of the obtained coating are relatively better.

[0063] Combining Example 2, Examples 12-13 and Table 2, it can be seen that the mass ratio of xylene and acetone in the solvent of Examples 12-13 is different from that of Example 2, and the reflectivity, emissivity and temperature drop values ​​of Examples 12-13 are significantly lower than those of Example 2, and the light aging color difference values ​​are significantly higher than those of Example 2. And combined with Comparative Example 6, the reflectivity, emissivity and temperature drop values ​​of Comparative Example 6 are significantly lower than those of Example 2, and the light aging color difference values ​​are significantly higher than those of Example 2.

[0064] From the above, it can be concluded that the compound of xylene and acetone as a solvent can significantly improve the thermal insulation effect and anti-ultraviolet aging performance of the coating; and when the mass ratio of xylene to acetone is 1:1, the thermal insulation effect and anti-ultraviolet aging performance of the obtained coating are relatively better.

[0065] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, all equivalent changes made according to the products, methods, and principles of the present application should be included in the protection scope of the present application.

Claims

1. A coating with low solar radiation absorption rate, characterized in that: Includes the following components and their contents: Reflective heat-insulating material 18-22wt%, infrared emitting material 5-7wt%, modified inorganic pigment 13-15wt%, organic binder 4-6wt%, heat-insulating auxiliary agent 4-6wt%, dispersing auxiliary agent 1-3wt%, and the balance is solvent; The reflective heat-insulating material comprises TiO2, BaSO4, ZnO and Eu2O in a mass ratio of 1: (0.8-1.0): (0.5-0.7): (0.3-0.5).

2. A coating with low solar radiation absorption rate according to claim 1, characterized in that: The infrared emitting material comprises Fe2O3-MnO2-NiO-Co2O3 composite nanometer powder, barite and brucite in a mass ratio of 1:(0.3-0.5):(0.1-0.3).

3. A coating with low solar radiation absorption rate according to claim 2, characterized in that: The preparation method of the infrared emitting material comprises the following steps: Mix Fe203, MnO2, NiO and Co203 and wet grind for 15-18h; take out, dry, grind and sieve to obtain powder; then calcine the powder at 1100-1200℃ for 1-2h, and grind to obtain Fe203-MnO2-NiO-Co203 composite nano powder; The Fe203-MnO2-NiO-Co203 composite nano powder, barite powder and brucite powder are mixed and wet-ground according to a mass ratio. After drying, the mixed product is crushed, ground and sieved to obtain an infrared emitting material.

4. The coating with low solar radiation absorption rate according to claim 1, characterized in that: The modified inorganic pigment is obtained by coating and modifying the inorganic pigment with potassium silicate.

5. A coating with low solar radiation absorption rate according to claim 4, characterized in that: The inorganic pigment is selected from at least one of titanium dioxide, aluminum powder, red iron oxide, lead chrome yellow, ultramarine and cobalt blue.

6. The coating with low solar radiation absorption rate according to claim 1, characterized in that: The organic binder is selected from at least one of methyl silicone resin, polymethylsiloxane and acrylic resin.

7. The coating with low solar radiation absorption rate according to claim 1, characterized in that: The dispersing aid comprises a silane coupling agent and an OP-10 emulsifier in a mass ratio of 1:(0.4-0.6).

8. The coating with low solar radiation absorption rate according to claim 1, characterized in that: The heat insulation auxiliary agent comprises hollow microspheres and polyurethane in a mass ratio of 1:(1.3-1.5).

9. A method for preparing a coating with low solar radiation absorption rate as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: The above-mentioned reflective heat-insulating material, infrared emitting material, modified inorganic pigment, organic binder and heat-insulating aid are sequentially added to the solvent and stirred for 1-2 minutes, then a dispersing aid is added and stirred for 1-2 minutes, and finally ultrasonically dispersed for 1-2 hours to obtain a coating.

10. A coating method for a coating with low solar radiation absorption rate as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: First, polish the substrate, then use ethanol to ultrasonically clean the substrate for 1 hour, and then dry it for later use; Then the prepared coating is coated on the substrate by air spraying, scraping or brushing with a coating thickness of 80-110 μm, and then cured at room temperature for 7-10 days.